Cobalt-Based Perovskite Electrodes for Solid Oxide Electrolysis Cells - Chi Zhang; Bin Lu; Haiji Xiong; Chengjun Lin; Lin Fang; Jile Fu; Dingrong Deng; Xiaohong Fan; Yi Li; Qi-Hui Wu (Inorganics, 2022)
Recently, many efforts and much attention has been paid to developing environmentally friendly energy. Solid oxide electrolyte cells (SOECs) process in reverse to solid oxide fuel cells (SOFCs) producing hydrogen gas as a green energy source. However, in this application, high-performance catalysts are usually required to overcome the sluggish oxygen evolution reactions (OER) during water decomposition. For this reason, discovery of catalysts with high performance is a crucial issue for the wide application of SOECs. Owning to their inherent activity and adequate stability in electrochemical conditions, perovskite oxides have been intensively employed in SOECs. In this mini review, we summarize the currently available studies concerning the applications of cobalt-based perovskite oxide catalysts in SOECs. Particularly, their structural properties and corresponding electronic structures are discussed based on their electrochemical performance, both experimentally and theoretically.